Pengungkapan Corporate Social Responsibility, Kinerja Lingkungan dan Nilai Perusahaan - Yuni Pramitha, Ida Ayu; Sudana, I Putu (E-Jurnal Akuntansi, 2021)
Firm value is an important performance indicator for publicly-listed companies. The purpose of this study is to empirically examine the effect of corporate social responsibility disclosure and environmental performance on firm value. Companies in consumer goods listed in Indonesia Stock Exchange are chosen as the focus of the study. Additionally, companies should participate in the Company Performance Assessment Program ranking. Sample is determined by a purposive sampling and data are analyzed with Multiple Linear Regression Analysis. This study concludes that corporate social responsibility disclosure has positive effect on firm value, implying conformity with agency theory, legitimacy theory, and stakeholder theory. Environmental performance is found has no effect on firm value. Practically, this study recommends that intensity of disclosure should be considered as an important part of management strategy in increasing firm value. Keywords: Corporate Social Responsibility  Disclosure; Environmental Performance; Firm Value .